2007
DOI: 10.22201/ib.20078706e.2007.002.299
|View full text |Cite
|
Sign up to set email alerts
|

Estructura poblacional de Chiton Articulatus en las Islas Pájaros y Venados de la Bahía de Mazatlán, Sinaloa, México

Abstract: Resumen. El propósito del presente trabajo fue contribuir al conocimiento biológico y pesquero de Chiton articulatus, especie que se captura artesanalmente en las costas de Mazatlán, Sinaloa. Se realizaron recolectas bimestrales en la zona intermareal de las islas Pájaros y Venados, de febrero a diciembre de 2000, durante las mareas más bajas. Las recolectas se realizaron en 4 sitios distintos, 2 en la zona protegida frente a la bahía Mazatlán y 2 en la zona expuesta de ambas islas; los ejemplares se trasladar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
7
0
5
Order By: Relevance
“…Estos resultados contrastan con experimentos similares con C. alboriatus donde el hábitat intermareal rocoso, limita el crecimiento y distribución del individuo (Baxter y Jones 1986, Flores-Campaña et al 2007. Muchos organismos que habitan la zona intermareal presentan patrones de distribución correlacionados con variables bióticas y abióticas que cambian según la altura intermareal (Baxter y Jones 1986, McMahon et al 1991.…”
Section: Rev Biodivers Neotropunclassified
“…Estos resultados contrastan con experimentos similares con C. alboriatus donde el hábitat intermareal rocoso, limita el crecimiento y distribución del individuo (Baxter y Jones 1986, Flores-Campaña et al 2007. Muchos organismos que habitan la zona intermareal presentan patrones de distribución correlacionados con variables bióticas y abióticas que cambian según la altura intermareal (Baxter y Jones 1986, McMahon et al 1991.…”
Section: Rev Biodivers Neotropunclassified
“…There was greater information available on the size structure of Chiton (C.) articulatus than any other species, since it is commercially important as mentioned by [14,22]; as is Chiton (C.) albolineatus in Mazatlan and the southwestern region on the Gulf of California stated by [16]. Regarding size structure for other species [15] reported that found no biometric information was found other than for Chiton (C.) articulatus, except for some data on size and referred to as total length.…”
Section: Body Measurementsmentioning
confidence: 99%
“…Despite their diversity and abundance, they are usually underestimated in faunal studies, probably due to the fact that they are not considered to be a species of commercial value and the little information we have for this type of organism, probably comes from the cryptic habitats where most species live, and the difficulties it presents in obtaining access to the area in which they are found in greater abundance [4]. There are global reports concerning Class POLYPLACOPHORA on a taxonomic scope and geographical distribution such as [5][6][7][8] for the American Pacific as [9,10], as well as those made in the Mexican coast zone as [3,4,[11][12][13]; other studies also found Chitons' ecological data as [14][15][16]. With respect to marine priority coastal regions in the State of Guerrero, [17] reported for Marine Priority Region No.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the size structure of C. articulatus as commercially important species was mentioned by [3,4,38,39]. Regarding to size structure for other chiton species, [38] reports that, no biometric information was found for other than C. articulatus.…”
Section: Size Structuresmentioning
confidence: 99%